Fundamentals of financial derivatives - Parasuraman (New Delhi Wiley India Pvt. Ltd., 2014)
This book has been primarily intended for the newcomer to the world of Derivatives. The aim is to provide a different approach to the learning of the complex instruments because many students and practitioners find Financial Derivatives too complex to understand in the beginning. The book deals with the basic techniques of risk management and derivatives. Encouraged by the overwhelming success of the first and second editions, the third edition has been brought out.
Keywords: Finance